Symbiotic microbial population composition of Apolygus lucorum under temperature and pesticide pressures - Ma, Mengxin; Xue, Hui; Zhu, Xiangzhen; Wang, Li; Niu, Lin; Luo, Junyu; Cui, Jinjie; Gao, Xueke (Frontiers in Microbiology, 2024)
Insect population control using pesticides faces new challenges as global temperatures change. Symbiotic bacteria of insects play a key role in insect resistance to pesticides, and these symbiotic bacteria themselves are sensitive to the effects of temperature changes. Apolygus lucorum, a sucking pest, survives in a wide range of temperatures (15°C–35°C), and is presently controlled predominantly using the pesticide imidacloprid. Here, we investigated the effects of temperature and imidacloprid on A. lucorum microbial population composition using 16S rRNA sequencing. We found that the application of imidacloprid in high-temperature environments led to an increase in the species diversity of bacteria in the body of A. lucorum. High temperatures may disrupt the symbiotic relationship between certain bacteria and A. lucorum, such as Cedecea neteri. High temperatures led to a decrease in the abundance of Cedecea neteri. Agathobaculum butyriciproducens, Advenella migardefenensis, and Akkermansia muciniphila were very sensitive to temperature and were strongly affected by temperature changes. Microorganisms that were greatly affected by the concentration of imidacloprid in the community include Aeromonas caviae and Akkermansia muciniphila. The aim of this study is to reveal the dynamics and diversity of symbiotic bacteria of A. lucorum treated with imidacloprid at a range of temperatures. These results provide insight into new strategies for pest control in a changing climate.